Assessment of students’ ability to represent determinants of health and health systems science content on concept maps in a pre-clerkship curriculum - Tovah Tripp; Miriam Hoffman; Mitchell Miller; Joshua S. Josephs (BMC Medical Education)
Abstract Background Hackensack Meridian School of Medicine (HMSOM) was founded on a vision of addressing the determinants of health (DoH) in the daily practice of medicine. The school has an active learning curriculum partially conducted through a small group modified problem-based-learning entitled Patient Presentation Problem-based-learning Curriculum (PPPC). This course includes a Monday discussion of a patient case and a Friday small group session includes concept mapping of the week's basic, clinical, and health systems science (HSS) content. To help students contextualize and bring HSS principles into practice, PPPC at HMSOM requires that concept maps include not just basic science content from the week but also explicitly HSS topics and the DoH. Methods We reviewed group concept maps from 7 pre-clerkship courses. There were an average of 18.9 group concept maps per course available to review, with roughly 8 students per group. We reviewed concept maps for inclusion of DoH icons and HSS content and followed the trend throughout each course of the pre-clerkship curriculum. Results HSS content appeared in 45% of group concept maps in the first pre-clerkship course, but did not appear in any concept maps in subsequent courses. DoH content was inconsistently present in group concept maps throughout the first three courses, increased towards the end of the first academic year, and then showed a steady decline towards the end of the pre-clerkship curriculum. Conclusions Students sometimes include DoH on their concept maps and this improves from the first three courses towards the end of the first academic year. However, students do not prioritize inclusion of DoH in their concept maps at the end of the pre-clerkship curriculum. HSS content is included in less than half of the concept maps in the first course, and then is not included in any group concept maps for the remainder of the curriculum. This may be due to a decreased focus on DoH and HSS, or related to students’ tiring of pre-clerkship curricular activities including concept mapping. Providing feedback to students on inclusion of DoH and HSS in concept mapping may help improve this skill prior to the start of clerkships.